Translocation ETS leukemia-acute myeloid leukemia 1 (TEL-AML1) gene fusion in childhood acute lymphoblastic leukemia - Sri Mulatsih; Yeow Liang; Allen Yeoh; Sutaryo Sutaryo; Sunarto Sunarto (Paediatrica Indonesiana, 2009)
Background Acute lymphoblastic leukemia (ALL) in childrenis a heterogeneous disease with different subtypes based on their cellular and molecular characteristics. This condition wouldinfluence the treatment outcome and subsequent risk for relapse. Accurate assignment of individual patients to risk groups is a critical issue for better outcome. TEL-AML1 gene fusion is themost frequent in childhood ALL.Objective The aim of this study was to investigate the incidenceofTEL-AML1 children with ALL in Sardjito Hospital.Methods This was a cross sectional study. In this preliminarystudy, we used nested reverse-transcriptase polymerase chainreaction (RT-PCR) to analyze the present of TEL-AML1 genefusion in bone marrow sample of childhood ALL patients.Results We analyzed 41 samples. Out of these, 30 (73%) wereamplified. Twenry three out of 30 ALL patients with good medicalrecord were analyzed for this gene fusion. Out of 30 patients, there were five patients (17%) with TEL-AML1-positive gene fusion and 25 (83%) were TEL-AML1-negative. Among five patients with TEL-AML1-positive gene fusion, four patients (80%) were one year to less than 10 year old. All of the patients (100%) were with leukocyte < 50x109/L.Conclusions TEL-AML1 gene fusion was found in 17 % ofsamples. This gene fusion was more frequent in standard risk group (based on age and leukocyte). These data must be clarified with more samples. RT-PCR must be apply in all center as one part of improving diagnostic quality, especially in managing leukemia patients.